Гетерогенно-каталітична трансестерифікація триолеату гліцерину в полі ультразвукових хвиль - Мельник, Юрій Романович; Старчевський, Роман Олегович (НТУ "ХПІ", 2016)
Досліджено реакцію трансестерифікації (алкоголізу) триолеату гліцерину бутан-1-олом у присутності гетерогенного каталізатора – оксиду феруму (ІІ). Показано, що застосування ультразвукових коливань при температурі понад 373К істотно підвищує конверсію триолеату гліцерину порівняно із здійсненням реакції за таких самих умов , але без ультразвуку. Показано, що здійснення реакції при надлишковому тиску або із барботуванням азоту через реакційну суміш нівелює ефект від застосування ультразвукових коливань. Також показано, що попередня обробка каталізатора – оксиду феруму (ІІ) – ультразвуковими хвилями є не ефективною.

The reaction transesterification of glycerol trioleate with butane-1-ol in the presence of a heterogeneous catalyst – ferric oxide (II) has been investigated. The effect of the previous ultrasonic treatment of catalyst and continuous ultrasound during transesterification reactions has been investigated. The using of ultrasonic vibrations in the temperature range 363–388K can increase the conversion of glycerol trioleate have been established. The application of ultrasonic vibrations at temperatures above 373K significantly increases the conversion of glycerol trioleate compared to the reaction under the same conditions but without ultrasound has been investigated. The application of ultrasonic vibrations at 383-388K can increase the conversion of glycerol trioleate from 59.2% to 69.6% and from 61.3% to 72.3% in accordance. The implementation reaction at excess pressure leads to a sharp decrease in conversion of glycerol trioleate compared to a process without ultrasound has been shown. The bubbling nitrogen through the reaction mixture eliminates the effect of the using of ultrasonic vibrations has been found. The conversion of glycerol trioleate while bubbling nitrogen in the field of ultrasonic waves is close to that which is achieved without the us ing of ultrasound. Pretreatment catalyst – ferric oxide (II) – ultrasonic waves are not effective has been established. The catalyst that has been treated with ultrasonic vibrations and kept 1–4 days, the act almost as a catalyst that not treated been of ultrasound, has been shown. Thus that the using of ultrasonic waves is an effective way to increase the activity of heterogeneous catalytic reactions transesterification has been established.
Heterogeneous catalytic transesterification of glycerol trioleate in the field of ultrasonic waves
Keywords: рослинні олії; лужні каталізатори; соняшникова олія; бутан-1-ол; оксид феруму (ІІ); sunflower oil; transesterification; butane-1-ol; glycerol trioleate; ferric oxide (II)